ANALISIS RHODAMIN B PADA LIPSTIK YANG BEREDAR DI PASAR KOTA MANADO - Mamoto, Lidya Valda; Fatimawali, Fatimawali; Citraningtyas, Gayatri (UNIVERSITAS SAM RATULANGI, 2013)
Rhodamin B is a synthetic dye that banned for use in cosmetics and is certified as ahazardous material according to Minister of Health of Indonesian Republic No.376/Menkes/Per/1990 because it cause liver damage, kidney and lymph glands damage,followed with anatomy changes such as organ enlargement. Rhodamin B dye is often usedfor food and beverage products. The study was conducted to identify Rhodamin B in lipstickin the market of Manado City. Samples was taken from 3 main market in Manado city,namely Karombasan market, Pasar 45 market, and Bersehati market. Samples were soakedwith amonia solution, then using wool yarn to extract rhodamin B dye, followed byidentification using thin layer chromatography (TLC) then detected with UV light 254 and366 nm. Rhodamin B was evaluated using UV-Vis spectrophotometry. The result shows that9 examined samples doesn’t contain rhodamin BKeywords : Rhodamin B, Lipstick, thin layer chromatography (TLC), UV-VisSpectrophotometry.